Microstrip Patch Antenna Array Design and Mutual Coupling Reduction for Wi-Fi and Wi-Max Applications - Hameed, Saja; Hassan A. Yasser; Ahmad H. Al-Shaheen (University of Thi-Qar Journal of Science, 2025)
The 5G multiple-input multiple-output (MIMO) microstrip antenna with isolation enhancement that is tiny and based on a BandPass metamaterial (BPM) is presented in this study. The expectation of higher data rates drove the development of fifth-generation (5G) mobile communication networks. The performance of a two-element microstrip antenna array with and without bandpass metamaterial is compared in this work. The antenna consists of two parts, with its radiators positioned to report the parallel direction. The array antenna's overall dimensions are small, measuring 40 × 72 × 1.6 mm3. The proposed isolated double patch parallel antenna produces bandwidth and mutual coupling equal to 11GHz and less than -30dB  at a frequency range from 1.5 to 6GHz, respectively, while the rectangular microstrip patch antenna array produces these values at 14.80 GHz and -55.94dB. When compared to the double microstrip parallel antenna, the double microstrip parallel antenna with BPM is superior in terms of mutual coupling. This increasing demand for faster data speeds in the rapidly changing field of mobile communication technologies is met by this creative antenna.